ZNACZENIE SAMORZĄDÓW W OCHRONIE ZABYTKÓW. PROPOZYCJE ZMIAN - Małgorzata Gwiazdowska (Ochrona Dziedzictwa Kulturowego, 2016)
Changes made to the administration system in Poland in the years 1989–1990 were aimed at decentralising state government and increasing the importance of local government bodies. The author of this article reckons that this idea has not been reflected in the Polish body of law yet. There are no legal regulations provided in the provisions of law – not only in terms of the legal situation of historic preservation offices but also with regard to deciding what should fall under the authority of local government bodies. Scope of duties of local government historic preservation officers working in separate offices should be similar to the one that individual departments have. Moreover, authority should no longer be granted on discretionary basis. A principle should be therefore formulated that everything what comes within the competence of historic preservation officers must comply with statutory legislation. If a local government body wants to be delegated either full or partial authority, it should prove that it has both organisational and financial capacity to exercise it. We should therefore work towards a complete solution which would be practical and possible to adopt on both state and regional scale.